Atomic Layer Deposited Ti2O3 Thin Films. Issue 10 (20th April 2022) - Manjunath, K.; Saraswat, A.; Samrat, D.; Rao, C. N. R.
Abstract: Ti2 O3 thin films have been prepared through atomic layer deposition and subjected to electrical resistivity measurements as a function of temperature. The as‐prepared films were stable for up to three weeks. In Ti2 O3 thin films, the insulator‐metal transition is observed at ∼80 K, with nearly 3–4 orders of magnitude change in resistivity. The anomalous increase in electrical resistivity in the films is in accordance with the two‐band model. However, the energy interval between the bands depending on the crystallographic c / a ratio leads to a change in electrical resistivity as a function of temperature. Abstract : Ti2 O3 thin films prepared using atomic layer deposition, exhibited insulator‐metal transition as a function of temperature.